2019
DOI: 10.3847/1538-4357/ab4b4a
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Magnetic Fields By the Synergies of Synchrotron Emission Gradients

Abstract: This paper studies how to employ synchrotron emission gradient techniques to reveal the properties of the magnetic field within the interstellar media. Based on data cubes of three-dimensional numerical simulations of magnetohydrodynamic turbulence, we explore spatial gradients of synchrotron emission diagnostics to trace the direction of the magnetic field. According to our simulations, multifarious diagnostics for synchrotron emission can effectively determine the potential direction of projected magnetic fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…As is shown in Figures 5, 6, 11 and 12, the anisotropic level of polarization intensity is relatively low at the frequency of 0.01 GHz, which makes the low-frequency polarized intensity more challenging to reveal the properties of MHD turbulence in the effect of the relevant noise and strong Faraday rotation. If the effect of small-scale noise-like is removed, we expect an increase in the degree of anisotropy, which should be similar to the scenario for the application of synchrotron polarization gradient techniques in the low frequency range (Zhang et al 2019a;2019b). The quadrupole ratio modulus and anisotropic coefficient used in this paper are complementary techniques to the gradient measurement.…”
Section: Discussionsupporting
confidence: 70%
“…As is shown in Figures 5, 6, 11 and 12, the anisotropic level of polarization intensity is relatively low at the frequency of 0.01 GHz, which makes the low-frequency polarized intensity more challenging to reveal the properties of MHD turbulence in the effect of the relevant noise and strong Faraday rotation. If the effect of small-scale noise-like is removed, we expect an increase in the degree of anisotropy, which should be similar to the scenario for the application of synchrotron polarization gradient techniques in the low frequency range (Zhang et al 2019a;2019b). The quadrupole ratio modulus and anisotropic coefficient used in this paper are complementary techniques to the gradient measurement.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, numerical resolution of data could influence the alignment measurements. We find that the projected magnetic field traced by gradient techniques is not subject to Faraday rotation, which is consistent with the situation for spatially coincident synchrotron polarization radiation and Faraday rotation (Zhang et al 2019a;Zhang, Liu & Lazarian 2019b). A comparison between the directions of projected magnetic field in the emitting-source region and the directions predicted by the gradient measurement of various diagnostics for Case A (see Figure 1).…”
Section: Case A: Faraday Rotation Effect In Foreground Regionsupporting
confidence: 82%
“…It is shown that the gradients of diagnostic techniques (P rad , P tang ) have a better alignment measurement compared with other diagnostic techniques. In view of our findings in Zhang, Liu & Lazarian (2019b) that the gradient of P rad has a robust ability for tracing magnetic field, P rad will be chosen to trace projected magnetic field in the following studies. Throughout this paper, we use a Gaussian kernel of less than 2𝜎 to smooth small scale noise-like structures.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations